Characterisation of Surface Ionisation and Adsorption of Phenol and 4-Nitrophenol on Non-Porous Carbon Blacks - P.J.M. Carrott; M.M.L. Ribeiro Carrott; T.S.C. Vale; L. Marques; J.M. Valente Nabais; P.A.M. Mourão; P.A.M. Suhas (Adsorption Science & Technology)
The adsorption of phenol and 4-nitrophenol from aqueous solutions by carbon blacks was studied. Particular attention was paid to the characterisation of the surface chemistry and ionisation of the carbon blacks by use of a simple carbon surface ionisation model, as well as the use of a normalised form of the Freundlich equation for the analysis of the adsorption isotherms. The results indicated that the solutes interact directly with the graphene layers and that the adsorption is sensitive to the π-electron density. Phenol has a weaker interaction and is more sensitive to the system conditions. In particular, it is more sensitive to oligomerisation under certain conditions. Comparison of the results with those previously reported for activated carbons with similar points of zero charge prepared from cork confirms the existence of a significant micropore-narrowing effect in the adsorption of organic solutes by activated carbons and which can lead to up to a doubling of the value of the Freundlich exponent, n F .